All gone : a memoir of my mother's dementia : with refreshments - Alex Witchel (Riverhead Books, 2012)
Just past 70, Witchel's smart, adoring, ultracapable mother began to exhibit undeniable signs of dementia. But as medical reality undid hope, Witchel retreated to the kitchen to come to terms with her predicamen